Why I don't write : and other stories - Minot, Susan (Alfred A. Knopf, 2020)
"A superb collection of short fiction--her first in thirty years and spanning many geographies--from the critically acclaimed author of Monkeys, Evening, and Thirty Girls A writer dryly catalogs the myriad reasons she cannot write; an artist bicycles through protests in lower Manhattan and ruminates on an elusive lover; an old woman on her deathbed calls out for a man other than her husband; a hapless fifteen-year-old boy finds himself in sexual peril; two young people in the 1990s fall helplessly in love, then bicker just as helplessly, tortured by jealousy and mistrust. In each of these stories Minot explores the difficult geometry of human relations, the lure of love and physical desire, and the lifelong quest for meaning and connection. Her characters are all searching for truth, in feeling and in action, as societal norms are upended and justice and coherence flounder. Urgent and immediate, precisely observed, deeply felt, and gorgeously written, the stories in Why I Don't Write showcase an author at the top of her form"--